Regional “sociology without sociologists” in the Middle Volga Region in the Soviet Period - M. V. Kildeev (Дискурс)
Introduction. The article analyzes circumstances of the emergence of regional sociology in the Soviet era. To describe this phenomenon, the author applies the concept of “sociology without sociology”. This idiom means scientific and sociological activity without the participation of the professional sociological community and describes this multivariate and non-linear process. The author also describes the reasons of existence of “sociology without sociologists” in Soviet and then in Russian social sciences. Methodology and sources. The category “sociology without sociologists”, used by R. Ahlberg, N. Werth, and J. Matthes describes the abnormal state of science. In addition, the author uses the concept of “public sociology” by M. Burawoy to determine the vectors of evolution of Soviet and Russian regional sociology. The main research method is the analysis of documentary sources of the Soviet era. Also new, previously unexplored archival documents have been introduced into scientific circulation. Results and discussion. The studied issue is examined on the ground of mass surveys of the state of religiosity of the population, which were initiated and carried out by the party bodies of the Tatarstan ASSR and Kuybishev area in 1964–1966. The results of those amateurish surveys served as a foundation for the development of sociology in the region. The article shows that throughout the existence of the “legal” regional sociology, in parallel with it, there were various forms of “sociology without sociologists”. The specificity of the Soviet period was that the existence of “sociology without sociologists” met the expectations of some CSPU circles, responsible for ideology tasks.Conclusion. The application of the category "sociology without sociologists" is of great importance for the implementation of the demarcation of scientific and non-scientific forms of social knowledge.